Efektifitas Pemberdayaan Program Pendidikan pada Lembaga Amil Zakat Baitul Maal Hidayatullah Kota Makassar - Ammar Munir; Zaenab Zaenab; Suriadi Saputra (Sekolah Tinggi Agama Islam (STAI) Al-Azhar Gowa, 2022)
This study aims to determine the effectiveness of empowering educational programs at the Baitul Maal Hidayatullah Amil Zakat Institution, Makassar City, South Sulawesi. This research is descriptive qualitative research, using the approach of sociology and Islamic economics. The research is located on Jl. Tamalannrea Raya No. 27A, Tamalanrea District, Makassar City. Methods of collecting data through observation, interviews, and documentation. The results of this study indicate that the educational empowerment program at Laznas BMH South Sulawesi Branch consists of two parts student school scholarships and student college scholarships. The concept of Education Program Empowerment at Laznas BMH South Sulawesi Branch has been distributed to several mustahik who are entitled to scholarships for education programs by Laznas BMH South Sulawesi Branch. The effectiveness of educational program empowerment can be seen from the effectiveness indicators, namely: 1) right on target in distributing zakat funds to poor and underprivileged must hike 2) encouraging by supporting the needs of must hike in the field of education. 3) improve the quality of academic and non-academic achievements of Mustahik